Pemberdayaan Masyarakat Desa Payunga melalui Pemanfaatan Ikan Nila (Oreochromis niloticus) sebagai Produk Camilan untuk Meningkatkan Pendapatan Masyarakat - Risna Podungge; Widi Candika Pakaya; Dewa Gede Eka Setiawan (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2026)
The Community Empowerment Program of Payunga Village in Processing Nile Tilapia (Oreochromis niloticus) into Snack Products to Increase Community Income was implemented as an effort to enhance the local economy through innovation in fishery product processing. Payunga Village has abundant tilapia resources; however, they have traditionally been used only as fresh food without further processing. This community service program aimed to improve local residents’ skills in processing tilapia into value-added products, specifically tilapia pempek, while also strengthening managerial capabilities and expanding marketing access through digital promotion. The implementation method included forming community and student groups, conducting technical training on tilapia processing, providing business management assistance, and introducing digital marketing strategies. The results showed significant improvement in participants’ production skills, entrepreneurship motivation, and awareness of product quality. The tilapia pempek product was well received by local consumers due to its unique flavor and affordable price. Furthermore, the program fostered community awareness of the importance of business diversification and the potential of creative rural economies. Overall, this program contributed to increasing income, strengthening family economies, and promoting sustainable local-based economic independence.